2010
DOI: 10.1080/09670874.2010.499479
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, age structure and reproductive patterns ofRattus norvegicusandMus musculusin two areas of the city of Buenos Aires

Abstract: The aim of this research was to compare the abundance, growth, age structure and reproductive patterns of Rattus norvegicus and Mus musculus populations of a shanty town and a parkland in the city of Buenos Aires, Argentina. Live trapping of rodents was conducted in each area every 2 months, from September 2006 to August 2007. Abundance of R. norvegicus and M. musculus was significantly higher in the shanty town than in the parkland. Abundance of both species showed significant differences between trapping ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
(38 reference statements)
1
32
0
Order By: Relevance
“…Shantytowns refer to areas inhabited by a very lowincome population that lives in precarious dwellings with an inadequate supply of basic urban services, such as garbage removal, sanitation networks, electricity, telephones, and plumbing (Fernández et al 2007;Vadell et al 2010;Hancke and Suárez 2014).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Shantytowns refer to areas inhabited by a very lowincome population that lives in precarious dwellings with an inadequate supply of basic urban services, such as garbage removal, sanitation networks, electricity, telephones, and plumbing (Fernández et al 2007;Vadell et al 2010;Hancke and Suárez 2014).…”
Section: Study Areamentioning
confidence: 99%
“…Parklands refer to public areas of recreation, where areas of spontaneous vegetation and woodlots with planted species are included in a matrix of grass or ornamental lawn (Cavia et al 2009;Vadell et al 2010). The parklands studied were located on the banks of the Río de la Plata River and the Riachuelo River, both of which allow the entry of native flora and fauna to an urban ecosystem (Cavia et al 2009).…”
Section: Study Areamentioning
confidence: 99%
“…They found that Norway rats were more common in shantytowns and parklands compared to industrial-residential neighborhoods and natural preserves [4]. Another study in the same city found that Norway rats were more abundant in shantytowns compared to parklands [5]. In Salzburg, Austria, Norway rats were trapped in a variety of urban locations with distinct environmental features [6].…”
Section: Introductionmentioning
confidence: 99%
“…In these areas, there are several shantytowns where both high values in the proportion of people who answered having seen rodents in their dwellings and neighborhood in the last quarter (Fig. 3c) and high abundance of commensal rodents had been previously documented (Coto 2001;Fernández et al 2007;Vadell et al 2010;Cavia et al 2012). Possibly, the existing rodent problems in these neighborhoods do not motivate people to claim to the City Government because they have other essential needs.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, both Bajomi (1993), Vadell et al (2010), and Tamayo-Uria et al (2013b) all observed seasonal cycles of abundance of rats (R. norvegicus and R. rattus) in urban areas, which were positively associated with average temperature. In the present study, the same pattern was observed.…”
Section: Discussionmentioning
confidence: 88%